Screening Tools for Depression and Anxiety in Patients with Chronic Obstructive Pulmonary Disease – A Systematic Review. (2nd November 2021) - Larsen, C. H.; Bendstrup, E.; Neergaard, M. A.
Abstract: The diagnosis of depression or anxiety is often difficult to establish in patients with Chronic Obstructive Pulmonary Disease (COPD) as many physical symptoms are shared. There is no consensus on a screening tool for depression and anxiety in patients with COPD. The aim of this systematic review is to review screening tools for depression and anxiety suitable for application among patients with COPD in the clinical setting. A systematic review was made using predefined search terms and eligibility criteria. Of 274 initially screened articles, seven studies were found eligible. Three depression screening tools (BASDEC, BDI-II and HADS-D) had a sensitivity of 100% and a specificity >85%. The best performing anxiety screening tool (GAI) had a sensitivity of 86% and a specificity of 78%. Three screening tools had acceptable psychometric properties according to sensitivity and specificity to detect depression among patients with COPD, but the screening tools for anxiety were of less quality. Further research in and validation of the screening tools is needed to recommend one specific tool.